Radiographic benefit and maintenance of clinical benefit with intravenous golimumab therapy in patients with active rheumatoid arthritis despite methotrexate therapy: results up to 1 year of the phase 3, randomised, multicentre, double blind, placebo controlled GO-FURTHER trial. Issue 12 (3rd September 2013) - Weinblatt, Michael E; Westhovens, Rene; Mendelsohn, Alan M; Kim, Lilianne; Lo, Kim Hung; Sheng, Shihong; Noonan, Lenore; Lu, Jiandong; Xu, Zhenhua; Leu, Jocelyn; Baker, Daniel; Bingham, Clifton O
Abstract : Objective: Report on radiographic effects and maintenance of clinical benefit with intravenous golimumab 2 mg/kg+methotrexate (MTX) for up to week (wk) 52 in active rheumatoid arthritis (RA). Methods: Patients (n=592) with active RA (≥6/66 swollen, ≥6/68 tender joints, C reactive protein (CRP) ≥1.0 mg/dL and positive for rheumatoid factor and/or anticyclic citrullinated protein antibody at screening) despite MTX ≥3 months (stable dose of 15–25 mg/week for ≥4 weeks) participated in this multicentre, international, randomised, double blind, placebo controlled, phase 3 study. Patients were randomised (2:1) to receive intravenous golimumab 2 mg/kg or placebo infusions at weeks 0 and 4 and then every 8 weeks; patients continued their stable MTX regimen. Placebo patients started golimumab 2 mg/kg at wk16 (early escape; <10% improvement in tender and swollen joints) or wk24 (crossover by design). Week 24 and wk52 radiographic (van der Heijde-Sharp (vdH-S) scores), clinical efficacy and safety data up to 1 year are reported here. Results: Significant and rapid clinical improvement was observed up to wk24 of intravenous golimumab therapy. Golimumab+MTX treated patients demonstrated less radiographic progression than placebo treated patients at wk24 (vdH-S score mean change 0.03 vs 1.09; p<0.001) and wk52 (0.13 vs 1.22; p=0.001). Among patients with ≥20% improvement in the American College of Rheumatology response criteria or who achieved a 'good' or 'moderate' response according to the 28 joint Disease Activity Score employing CRP at wk24, approximately 80% maintained this response up until wk52. Through an average of 43.5 weeks of follow-up, 64.6% of patients receiving golimumab+MTX reported adverse events, most commonly non-serious infections. Conclusions: In patients with active RA despite MTX, intravenous golimumab+MTX yielded significant inhibition of structural damage at wk24 and wk52, and sustained clinical improvement in signs and symptoms with no new safety signals up to 1 year. ClinicalTrials.gov: NCT00973479, EudraCT 2008–006 064–11.